What Are Educational Indicators and Indicator Systems? - Richard J. Shavelson; L. McDonnell; J. Oakes (Practical Assessment, Research, and Evaluation, 1990)
Accessed 62,450 times on https://pareonline.net from November 13, 1999 to December 31, 2019. For downloads from January 1, 2020 forward, please click on the PlumX Metrics link to the right.
Keywords: *Educational Assessment; Educational Policy; Educational Trends; Elementary Secondary Education; *Evaluation Criteria; Evaluation Methods; Heuristics; Long Range Planning; *Management Information Systems; Outcomes of Education; *Statistical Data; Student